2023
DOI: 10.1038/s41467-023-36185-w
|View full text |Cite
|
Sign up to set email alerts
|

Defective excitation-contraction coupling and mitochondrial respiration precede mitochondrial Ca2+ accumulation in spinobulbar muscular atrophy skeletal muscle

Abstract: Polyglutamine expansion in the androgen receptor (AR) causes spinobulbar muscular atrophy (SBMA). Skeletal muscle is a primary site of toxicity; however, the current understanding of the early pathological processes that occur and how they unfold during disease progression remains limited. Using transgenic and knock-in mice and patient-derived muscle biopsies, we show that SBMA mice in the presymptomatic stage develop a respiratory defect matching defective expression of genes involved in excitation-contractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In addition, we found that all categories were enriched for terms associated with the endoplasmic reticulum and Golgi apparatus, including vesicular transport between the 2 organelles. In line with data identifying altered expression of genes regulating muscle structure and contraction across several SBMA mouse models ( 74 ), our GO analysis was enriched for terms related to cytoskeletal and contractile elements of the muscle fiber, including actin and elements of the sarcomere. GO analysis of downregulated proteins showed enrichment for terms associated with spermine biosynthetic process and glucose catabolic process to lactate via pyruvate ( Supplemental Table 3 ).…”
Section: Resultsmentioning
confidence: 53%
“…In addition, we found that all categories were enriched for terms associated with the endoplasmic reticulum and Golgi apparatus, including vesicular transport between the 2 organelles. In line with data identifying altered expression of genes regulating muscle structure and contraction across several SBMA mouse models ( 74 ), our GO analysis was enriched for terms related to cytoskeletal and contractile elements of the muscle fiber, including actin and elements of the sarcomere. GO analysis of downregulated proteins showed enrichment for terms associated with spermine biosynthetic process and glucose catabolic process to lactate via pyruvate ( Supplemental Table 3 ).…”
Section: Resultsmentioning
confidence: 53%
“…We asked whether LSD1 and PRMT6 are aberrantly expressed in tissues that degenerate in SBMA, including skeletal muscle, liver, spinal cord, brainstem, and heart 5 . To address this question, we used transgenic mice expressing human AR100Q that we recently generated and characterized 28,29 , knock-in SBMA mice in which AR exon 1 was replaced with the human AR exon 1 coding for a polyQ-expanded AR with 113Q 10 , and available patient biopsies (Supplementary Table 1). AR100Q male mice are non-symptomatic at 4 weeks of age (pre-symptomatic stage), start to show signs of muscle atrophy and motor dysfunction by 8 weeks of age (onset), and manifest signs of denervation by 12 weeks of age (late stage).…”
Section: Lsd1 and Prmt6 Are Induced By Androgens In Sbma Skeletal Musclementioning
confidence: 99%
“…It has also been demonstrated that the skeletal muscles of SBMA knock-in mice show metabolic changes such as increased lipid metabolism and impaired glycolysis prior to denervation (Rocchi et al , 2016). Furthermore, presymptomatic SBMA transgenic mice (AR-100Q) show early changes in the expression pattern of genes involved in muscle contraction and structure (Marchioretti et al , 2023).…”
Section: Introductionmentioning
confidence: 99%